2014
DOI: 10.1186/s12870-014-0375-3
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale investigation of mealiness in apple: an atypical role for a pectin methylesterase during fruit maturation

Abstract: BackgroundApple fruit mealiness is one of the most important textural problems that results from an undesirable ripening process during storage. This phenotype is characterized by textural deterioration described as soft, grainy and dry fruit. Despite several studies, little is known about mealiness development and the associated molecular events. In this study, we integrated phenotypic, microscopic, transcriptomic and biochemical analyses to gain insights into the molecular basis of mealiness development.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 70 publications
4
48
0
1
Order By: Relevance
“…It has been suggested that MdAF3 is involved in mealiness (Nobile et al, 2011). However, Segonne et al (2014) did not observe consistent MdAF3 expression profiles using three mealy/non-mealy pairs for comparison. The MdPG1 expression level increased in mealy fruit only after four months of cold storage, suggesting that it is involved in the process during the later storage stages (Segonne et al, 2014).…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…It has been suggested that MdAF3 is involved in mealiness (Nobile et al, 2011). However, Segonne et al (2014) did not observe consistent MdAF3 expression profiles using three mealy/non-mealy pairs for comparison. The MdPG1 expression level increased in mealy fruit only after four months of cold storage, suggesting that it is involved in the process during the later storage stages (Segonne et al, 2014).…”
Section: Introductionmentioning
confidence: 62%
“…The second most significant SNPs, SNP_FB_0832810 and SNP_FB_0832819, were located on the contig flanking the MdPG1. MdPG1 weakens the cellular adhesion in fruit (Atkinson et al, 2012) and could be involved in mealiness development during prolonged storage (Segonne et al, 2014). As our storage conditions were sufficient for expression of MdPG1 (20°C, 4 weeks), the MdPG1 may be the causal gene underlying QTL on chr 10, detected both in the QTL analysis and GWAS.…”
Section: Gwas For the Admmentioning
confidence: 93%
See 3 more Smart Citations